Medical Coercive Measures Under the Albanian Legislation and their Application to Criminally Irresponsible Individuals - Kreshnik Myftari; Gëzim Myftari; Sevada Guço (Institute of Medico-legal Publications Pvt Ltd, 2021)
Individuals, who are characterized by mental disorders and manifest them in a criminal behavior, cannot besubjects to the same punitive regime provided for other subjects of criminal offenses. Neither penitentiaryinstitutions nor civilian psychiatric hospitals are suitable for these individuals; the former, because theyare conceived only for that category of subjects who culpably violate criminal norms; second, because,since psychiatric hospitals have therapeutic purposes, they are not suitable for controlling the social risk ofirresponsible subjects.Any decision of irresponsibility due to mental state brings a certain consequence, namely the dismissalof the case and the imposition of coercive measure. The defendant, due to his social danger, may undergooutpatient treatment or compulsory treatment in a medical institution.The following manuscript analyzes the importance of medical coercive measures provided by the criminallegislation and at the same time, their importance in the treatment of irresponsible persons, perpetratorsof criminal offenses. It tries to give an overview of the different orientations that characterize the issue inquestion, to underline the conclusions reached by jurisprudence and at the same time to reason not only onthe basis of applicable norms, but also on the basis of perspective and opportunity for reform, seeking todevelop points of reflection and avoid unreasonable discussions.